Pengaruh Disiplin Kerja dan Motivasi Terhadap Kinerja Karyawan pada PT Supra Primatama Nusantara (Biznet) Branch Duri Pulo Jakarta Pusat. - Pusporini Palupi Jamaludin; Laura Komala; Adi Martono (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to determine the Influence of Work Discipline and Motivation on Employee Performance at PT Supra Primatama Nusantara (Biznet) Branch Duri Pulo Central Jakarta. The type of research used in this study is quantitative research. The population used in this study were employees of PT Supra Primatama Nusantara (Biznet) Branch Duri Pulo Central Jakarta. The sample used by the author in this study was employees of PT Supra Primatama Nusantara (Biznet) Branch Duri Pulo Central Jakarta totaling 54 employees. The data collection method used in this study is primary data. The primary data taken is data from the answers of 54 respondents. The results of this study indicate that partially there is a significant influence between discipline on employee performance at PT Supra Primatama Nusantara (Biznet) Branch Duri Pulo Central Jakarta, as evidenced by the calculated t value> t table or (3.109> 2.007) This is also reinforced by the Sig. value <0.05 or (0.003 <0.05). Partially there is a significant influence between motivation on employee performance at PT Supra Primatama Nusantara (Biznet) Branch Duri Pulo Central Jakarta., which is evidenced by the calculated t value> t table or (2.080> 2.007) This is also reinforced by the Sig. value <0.05 or (0.043 <0.05). Simultaneously there is a significant simultaneous influence between discipline and motivation on employee performance at PT Supra Primatama Nusantara (Biznet) Branch Duri Pulo Central Jakarta, which is evidenced by the calculated F value> F table or (20.508> 3.179), this is also reinforced by the Sig. value <0.05 or (0.000 <0.05). The coefficient value of R is 0.668, which means that the relationship between the Discipline and Motivation variables on the Employee Performance variable is strong. The value of the determination coefficient or contribution of its influence simultaneously is 44.6% while the remaining 55.4% is influenced by other factors.